The Impact of Transformational Leadership Style on ASN Performance with Work Motivation Mediation at OPD Jember Regency - Nurul Fawaid; Fitria Dwi; Arief Junaedi; Nursaid; Nurul Qomariah (www.amertainstitute.com, 2024)
State Civil Apparatus (ASN) are civil servants who must provide the best service to the community who need services. These ASN are required to be pioneers in order to be able to overcome problems in all fields. ASN must have high quality, dedication, and work ethic. This study aims to determine the effect of leadership style on ASN performance through work motivation at the Jember Regency Government. The population in this study were all Leaders of Regional Apparatus Organizations (OPD) totaling 72 people. Saturated samples as a sampling technique. With descriptive analysis, validity and reliability tests, and hypothesis tests, this study was carried out. This study resulted in that transformational leadership style had an effect on work motivation. Transformational leadership style had a positive and significant effect on ASN performance. Employee work motivation had an impact on ASN performance at the Jember Regency Government OPD. Transformational leadership style had a positive and significant effect on ASN performance through work motivation..